Genetic structure and phylogenetic relationships of Phyllidiellapustulosa species from Seribu Islands, North Sulawesi, Halmahera, and West Papua. Issue 1 (December 2021) - Yonatika, N O; Widiasih, N; Hamidah, M; Nurhakim, M D; Budiarto, H; Bintang, D M C; Sani, L M I; Lestari, D F; Setyaningsih, W A; Subhan, B; Madduppa, H
Abstract: Phyllidiella pustulosa are brightly coloured gastropod molluscs frequently found in coral reefs of the tropical Indo-Pacific. Phyllidiella pustulosa is widely distributed in Indonesia, such as Seribu Island, North Sulawesi, West Papua, and Halmahera. Based on the genetic characteristics of an individual's DNA sequence, differences between species can be identified. In this paper, we would like to provide the molecular analysis and phylogenetic relationship among nudibranchs from Indonesian waters. Identification was made by measuring the genetic distance between species. The phylogenetic tree reconstruction was made using the Kimura 2-parameter model with 1000 times bootstrap with neighbor-joining and maximum likelihood method. There is 46 DNA Sequence obtained from 4 different regions (Seribu Island, Halmahera, North Sulawesi, and West Papua). The genetic distance of West Papua and Halmahera has the smallest value among other populations, which is between 0.0051-1.4629, compared to the population in Halmahera. The phylogenetic tree also shows populations from West Papua and Halmahera are on the same lineage, indicating that the population in West Papua and Halmahera had the closest relation. The study suggested that North Sulawesi, Halmahera and West Papua have genetic mixing of the same region, which is distinctive from Seribu Island.